Disinfestation and in vitro establishment of “Thap maeo” (AAB subgroup) banana explants submitted to chlorine concentrations - Pereira, Gustavo Alves; Boliani, Aparecida Conceição; Correa, Luiz Souza (Comunicata Scientiae, 2015)
Most of banana plantations are still carried out using traditional seedlings types, named in Brazil as ‘chifrinho’, ‘chifre’, ‘chifrão’ (with a literal translation of little horn, horn and big horn, respectivelly) and also using rizoma pieces. Other propagation methods, such as micropropagation, have been developed and improved in order to increase the multiplication rate in a short period of time and improve the seedlings phytossanitary canditions. The aim of this study was to evaluate the ‘in vitro’ disinfection using active chlorine concentrations in explants of ‘Thap maeo’ bananas , which is a viriety resistant to black and yellow Sigatokas, as well as Panama disease. The treatments were: T1 – control without active chlorine , T2 - 0.5% of active chlorine, T3 - 1.0% of active chlorine, T4 - 1.5% of active chlorine and T5 - 2% of active chlorine. The percentage of contamination by bacteria and fungi as well as the percentage of oxidation of the explants were evaluated. It was concluded that the highest efficiency among treatments was the T5 – immersion of the explants in 2% of active chlorine, whichresullted in 82% and 88% of reduction, respectively, for bacteria and fungi.